1998
DOI: 10.1007/bf02737120
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal plasticity involves extensive gene induction and multiple cellular mechanisms

Abstract: Long-term plasticity of the central nervous system (CNS) involves induction of a set of genes whose identity is incompletely characterized. To identify candidate plasticity-related genes (CPGs), we conducted an exhaustive screen for genes that undergo induction or downregulation in the hippocampus dentate gyrus (DG) following animal treatment with the potent glutamate analog, kainate. The screen yielded 362 upregulated CPGs and 41 downregulated transcripts (dCPGs). Of these, 66 CPGs and 5 dCPGs are known genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 125 publications
7
120
1
Order By: Relevance
“…The VGF gene has a CREB binding site, which is necessary for its induction by other neurotrophic factors (Salton et al, 2000), and suggests a point of convergence for transcriptional regulation by 5-HT and BDNF. Furthermore, expression of VGF is induced by BDNF (Eagleson et al, 2001;Alder et al, 2003) as well as in models of neuronal activity such as learning, LTP, seizure, and synaptogenesis (Lombardo et al, 1995;Benson and Salton, 1996;Hevroni et al, 1998;Snyder et al, 1998;Alder et al, 2003;Newton et al, 2003;Altar et al, 2004). In support of our findings of an increase in VGF expression after imipramine treatment, an increase in VGF mRNA was observed in the hippocampus of animals after electroconvulsive therapy (Newton et al, 2003;Altar et al, 2004;Conti et al, 2007).…”
Section: Vgf In Depression Modelssupporting
confidence: 82%
“…The VGF gene has a CREB binding site, which is necessary for its induction by other neurotrophic factors (Salton et al, 2000), and suggests a point of convergence for transcriptional regulation by 5-HT and BDNF. Furthermore, expression of VGF is induced by BDNF (Eagleson et al, 2001;Alder et al, 2003) as well as in models of neuronal activity such as learning, LTP, seizure, and synaptogenesis (Lombardo et al, 1995;Benson and Salton, 1996;Hevroni et al, 1998;Snyder et al, 1998;Alder et al, 2003;Newton et al, 2003;Altar et al, 2004). In support of our findings of an increase in VGF expression after imipramine treatment, an increase in VGF mRNA was observed in the hippocampus of animals after electroconvulsive therapy (Newton et al, 2003;Altar et al, 2004;Conti et al, 2007).…”
Section: Vgf In Depression Modelssupporting
confidence: 82%
“…However, the exact mechanisms for the rapid and robust downregulation of BICC1 mRNA in BICC1 expression is elevated in depressed subjects KT Ota et al response to ketamine and KCl treatment will require additional studies. The activity-dependent downregulation of BICC1 is particularly interesting as genes showing activityinduced downregulation are relatively rare: they are an order of magnitude lower in abundance than genes showing activity-dependent upregulation (Hevroni et al, 1998;West et al, 2002). Here, we also show that the downregulation of BICC1 is functionally relevant, as knockdown of BICC1 in the hippocampus is sufficient to rescue anhedonic behavior in CUS-treated rats.…”
Section: Discussionmentioning
confidence: 53%
“…The two genes show overlapping expression patterns, although DCLK is more widely expressed in the brain (Sossey-Alaoui and Srivastava, 1999;Burgess and Reiner, 2000). In addition, DCLK encodes multiple transcripts, which are all differently regulated and may have different functions (Hevroni et al, 1998;Burgess et al, 1999;Silverman et al, 1999;Vreugdenhil et al, 2001;Burgess and Reiner, 2002). Two groups have recently reported that, although Dcx or Dclk mutant mice do not show defects in radial neuronal migration, mutants for both Dcx and Dclk genes display cortical lamination defects, suggesting that they can functionally compensate each other (Deuel et al, 2006;Koizumi et al, 2006a).…”
Section: Dclk Rnai Results In a Decrease In The Number Of Interneuronmentioning
confidence: 99%